Isothiocyanates in medicine: A comprehensive review on phenylethyl-, allyl-, and benzyl-isothiocyanates - Cosima C. Hoch; Maria Shoykhet; Tobias Weiser; Lena Griesbaum; Julie Petry; Khouloud Hachani; Gabriele Multhoff; Ali Bashiri Dezfouli; Barbara Wollenberg (Elsevier, 2024)
In recent years, isothiocyanates (ITCs), bioactive compounds primarily derived from Brassicaceae vegetables and herbs, have gained significant attention within the biomedical field due to their versatile biological effects. This comprehensive review provides an in-depth exploration of the therapeutic potential and individual biological mechanisms of the three specific ITCs phenylethyl isothiocyanate (PEITC), allyl isothiocyanate (AITC), and benzyl isothiocyanate (BITC), as well as their collective impact within the formulation of ANGOCIN® Anti-Infekt N (Angocin). Angocin comprises horseradish root (Armoracia rusticanae radix, 80 mg) and nasturtium (Tropaeoli majoris herba, 200 mg) and is authorized for treating inflammatory diseases affecting the respiratory and urinary tract. The antimicrobial efficacy of this substance has been confirmed both in vitro and in various clinical trials, with its primary effectiveness attributed to ITCs. PEITC, AITC, and BITC exhibit a wide array of health benefits, including potent anti-inflammatory, antioxidant, and antimicrobial properties, along with noteworthy anticancer potentials. Moreover, we highlight their ability to modulate critical biochemical pathways, such as the nuclear factor erythroid 2-related factor 2 (Nrf2)/Kelch-like ECH-associated protein 1 (Keap1), nuclear factor kappa-light-chain-enhancer of activated B cells (NF-κB), and signal transducer and activator of transcription (STAT) pathways, shedding light on their involvement in cellular apoptosis and their intricate role to guide immune responses.